Droughts, cereal prices, and price stabilization options - Dorosh, Paul A.; Smart, Jenny; Minten, Bart; Stifel, David (International Food Policy Research Institute, 2020)
Chapter 9, “Droughts, Cereal Prices, and Price Stabilization Options,” looks at price volatility, causes, and policy options. Increases in cereal prices in Ethiopia often raise concerns about adverse effects for poor net consumers. In particular, the frequent natural calamities—especially droughts—in Ethiopia can lead to important price hikes. But domestic prices of some cereals (especially maize) fluctuate every year with prices at harvest times substantially dropping, to the detriment of producers. Price stabilization efforts are therefore an important consideration for Ethiopian policymakers. This chapter sheds light on options for cereal price stabilization in Ethiopia drawing on experiences of other developing countries. The international experience in food price stabilization shows that while some countries have achieved success, the efforts of many others have actually destabilized market prices at great fiscal costs. When assessing the extent to which price stabilization efforts in Ethiopia were effective during the major El Niño–induced droughts of 2015 and 2016 (including food aid distributed through the PSNP), the authors find that an opportunity was missed to enhance food security and consumer welfare by allowing private-sector imports to minimize the rise in cereal prices as well as to reduce the fiscal costs to the government and donors.